Universal and Specific Predictors of Chinese Children With Dyslexia – Exploring the Cognitive Deficits and Subtypes - Song, Shuang; Zhang, Yuping; Shu, Hua; Su, Mengmeng; McBride, Catherine (Frontiers in Psychology, 2020)
While previous studies have shown that the impact of phonological awareness and rapid automatized naming (RAN) on dyslexia depends on orthographic complexity in alphabetic languages, it remains unclear whether this relationship generalizes to the more complex orthography of Chinese. We investigated the predictive power of phonological awareness, RAN, and morphological awareness in dyslexia diagnosis status in a sample of 241 typically developing and 223 dyslexic Chinese-speaking children. A logistic regression analysis showed that phonological awareness and RAN were both significant predictors of dyslexia status, while morphological awareness played a comparatively more important role for Chinese children. Further cluster analysis identified four subtypes of dyslexia in this sample: a global deficit group, a phonological deficit group, a RAN deficit group, and a mild morphological deficit group. Our findings are largely consistent with previous studies of predictors of dyslexia, while uniquely demonstrating the predominant effect of morphological awareness in Chinese reading.